SISTEM INFORMASI PENJUALAN PADA TOKO BUKU KRISTEN GRACIAS BERBASIS APLIKASI DESKTOP - Betesda Betesda (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2023)
ABSTRACTGracias Christian Bookstore is a Christian bookstore engaged in the sale of books, stationery, and items related to church needs or supplies. Christian Gracias Bookstore uses a manual recording system when carrying out the buying, selling, and making transaction reports that still use books. The use of a manual recording system in the purchasing process and the preparation of transaction reports greatly influences the Bookstore Report and also on customer satisfaction because customers now get receipts instead of receipts or receipts as usual. It is time for the Gracias Christian Bookstore to improve the system it uses, because a computerized information system is very useful for computerized and modern buyer receipts, and for the admin it is easier to make Transaction Reports to be reported to the Owner of the Gracias Christian Bookstore, and the owner of this Bookstore too has the right to have access rights to view every activity of Reports on the Purchase and Sale of Goods, and other Transactions. The research method used in making this proposal report is through direct observation at the research location, and the Waterfall method is a basic process that involves specification, development, validation, solutions, and represents as different processes such as requirements specification, software design, implementation, and testing. The system design will be explained in the proposed system procedure, the proposed system procedure will be implemented using UML, database design, proposed system interface design, proposed system configuration, proposed implementation, and blackbox testing. Implementation of information systems to satisfy customers, because currently customers get receipts in printed form, there are no blank bills written in pen, and especially Sales transactions can improve Bookstore performance by making it easier to process Sales transaction reports with a computerized system.Â Keywords: Sales Information System, Sales Notes, Sales Reports.Â